Ecological sustainability of smallholder dairy farm with Leisa pattern - Asminaya, N. S.; Purwanto, B. P.; Nahrowi, N.; Ridwan, W. A.; Atabany, A. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
This study was conducted to determine the sustainability status of smallholder dairy farms applying Low External Input Sustainable Agriculture (LEISA) pattern, and to formulate sustainable model. Eight smallholder dairy farms located in livestock business area (KUNAK) were purposive selectedwith criteria was they had 11 heads dairy cows, planted an elephant grass, dispose the manure to grassland, did not use chemicals fertilizer, 4250 m2 land area of dairy farming. Data were analyzed by: 1) attribute determination, 2) ordinal scale determination based on sustainability criteria;3) data analysis (Rap Dairy software);4) assessment of index and sustainability status;5) review sensitive attributes (leverage analysis)and 6) validation model (Monte Carloand Square Correlation (SQR) analysis). Attributes and ordinal scale on ecological sustainability weredensityof dairy cow, carrying capacity, supply water, drainage cages, soil fertility, topography, rainfall, humidity, temperature and altitude. Results of Rap Dairy analysis showed that smallholder dairy farms who apply LEISA pattern ecologically was quite sustainable with index of 57.95.The index could be increased to 88.39 (sustainable) through model simulation with respect to sensitive attributes. The results of Leverage analysis showedthat topography, densityof dairy cow, carrying capacity, supply water availability were sensitive attributes.Analysis Monte Carlo and SQR showedthat model could explain data well.